Studi perbandingan elektroda bawah air konvensional dan elektroda dengan modifikasi tambahan mg - Hindami, Fahrizan Imam; Winarto, Winarto; Purnama, Dewin (Jurnal Mesin Nusantara, 2023)
The influence of water depth, microstructure, chemical composition, welding defects, and mechanical properties affect underwater welding. In addition, the determination of electrodes for underwater welding requires unique properties, including being able to cause arcing and slag to grow on the surface of metal deposits which can protect against the effects of oxides and low hydrogen solubility. The electrodes must meet the AWS D3.6M underwater welding specification standard. In this study, the steel plate material used in AH-36 and implemented for underwater wet welding by comparing two electrodes, namely E6013 with additional Mg modifications and Broco E70XX electrodes specifically for underwater wet welding, the other Mg on E6013 rutile electrodes with modification 1 ( 3% Mg) and Modification 2 (5% Mg). The welding method with a heat input of 1.5 kJ/mm with 130 A and 2.5 kJ/mm with 140 A is carried out at 5m. The radiographic test results showed that the welded specimens at a depth of 5m showed imperfect penetration defects. It may be due to the effect of significant pressure and higher cooling rate that the weld melt cannot penetrate completely into the parent material. The tensile test results also showed an insignificant increase in the strength of the underwater welding, and the elongation was quite significant. Occurs at the E6013 electrode with modification 1 (3% Mg) and Modification 2 (5% Mg). The increase is not too significant. Penetration is not perfect. Due to significant pressure and a higher cooling rate, the molten weld cannot penetrate completely into the parent material. However, for testing the Broco E70XX electrode where there is no change in microstructure, such as electrodes modified with magnesium where only grain growth occurs, and there is Spheroidite which makes the microstructure related to mechanical properties, namely ductile.